Pengaruh Silica Fume dan Pecahan Batu Marmer Sebagai Bahan Subtitusi Pada Campuran Beton - Elli Mercy Julmile; Frans Phengkarsa; Suryanti Rapang Tonapa (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
The aim of this study was to determine the effect of using silica fume and marble stone fragments as substitution materials in concrete mixtures on split tensile strength, concrete flexural strength and compressive strength.. Testing test objects are split tensile strength, bending strength, and compressive strength. In this study, the quality of concrete is planned, which is 25 MPa.From the results of the study, the compressive strength value of concrete for variations in marble fragments was 50% and Silica Fume was 0%, 10%, 12.5% and 15%, namely 25,175 MPa, 25,832 MPa, 24,606 MPa and 24,229 MPa, testing the tensile strength of splits for variations in marble fragments by 50% and Silica Fume by 0%, 10%, 12.5% and 15% was 1,886 MPa, 1,909 MPa, 1,862 MPa and 1,815 MPa, bending strength test for variations in marble shards by 50% and Silica Fume by 0%, 10%, 12.5% and 15% by 25,175 MPa, 25,832 MPa, 24,606 MPa and 24,229 MPa. The effect of the substitution of marble fragments as coarse aggregates by 50% and the substitution of silica fume as cement with variations of 0%, 10%, 12.5% and 15% on the values of compressive strength, tensile strength, and bending strength of concrete obtained the maximum value of silica fume substitution at a variation of 10% and decreased in strength above the variation of silica fume 10%, the higher the percentage of silica fume substitution, the lower the strength of concrete.